PENERAPAN MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA DI RUMAH SAKIT ISLAM SURABAYA A. YANI - Muhammad Huda Firmansyah (Jurnal Kesehatan Masyarakat (Undip), 2022)
Risk management is a preventive effort for a company, especially those engaged in the service sector, which is very prone to errors and complaints. For this reason, it is necessary to map the risks that occur in accordance with the work unit in it which is expected to minimize the number of accidents or errors in both patients, visitors and employees in the hospital. In the 2019 patient safety incident report data at the Surabaya A. Yani Islamic Hospital, it was found that there were incidents which included near miss 93%, not injured 4%, unexpected events 3% and Sentinel 0%. The purpose of this study was to identify and identify the application of occupational safety and health risk management at the A. Yani Islamic Hospital in Surabaya. This thesis is a qualitative research with a case study method with the aim of fully describing the implementation of K3 risk management at Surabaya A. Yani Hospital based on observation, survey and documentation data on 37 units and hospital workplaces by identifying risks. , analyze and find risk control measures. The results showed that the implementation of K3 risk management in the Islamic Hospital of Surabaya A. Yani based on the results of risk identification obtained as many as 25 risks in the graha building and the old building which were further analyzed by finding 15 moderate risks and 10 high risks. can be done is by repairing damaged infrastructure and improving the existing security system at the A. Yani Islamic Hospital in Surabaya. The conclusion in this study is the implementation of K3 risk management at the Islamic Hospital of Surabaya A. Yani based on the process of risk identification and risk analysis, there are 25 potential risks, of which there are 15 moderate risks and 10 high risks that can potentially cause accidents to employees, visitors and patients. In this case, control efforts are made to minimize the number of incidents and accidents.